Uji Coba Metode Check List Pada Evaluasi Kinerja Karyawan PT. IKPP Serang Mill Seksi Raw Material Warehouse - Aang Kunaifi; Indah Friska; Syamsul Hidayat (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to conduct a pilot evaluation of employee performance in the Raw Material Warehouse Section at PT. IKPP Serang Mill using a checklist-based performance appraisal model. Performance evaluation is a crucial aspect in ensuring the smooth operation of raw material warehouses, which involve a high level of occupational risk and have a direct impact on the continuity of the production process. The checklist method is applied because it integrates quantitative assessment through scoring results with qualitative evaluation in the form of behavioral feedback. This study employs a qualitative descriptive approach supported by quantitative data obtained from performance assessments of ten employees holding various positions, including forklift operators, checkers, shift administrators, and shift supervisors. The results indicate that employee performance falls within a diverse spectrum, categorized as “performance” and “need to improve,” influenced by compliance with standard operating procedures (SOPs), work discipline, communication, and awareness of occupational health and safety (OHS). The findings also demonstrate that the checklist-based model is effective in identifying performance gaps and serves as a basis for formulating improvement actions such as coaching, OHS training, promotions, and administrative sanctions. This study concludes that the checklist model functions not only as an administrative evaluation tool but also as a strategic instrument for human resource development and sustainable organizational performance improvement.